Empowering Speaking Skills through Speaking Assessment in the Process of ELT in Think-E Course - Amy Krisdiana (Pioneer: Journal of Language and Literature, 2021)
There are some kinds of speaking assessments, the accuracy in choosing the type of assessment determines the success of the student in speaking English. This can be seen in Think-E course, Think-E course is successful in choosing the type of assessment so that the students in Think-E course can speak English fluently. The aim of the study is to describe types of assessments used in the English language Teaching at Think-E course, and how this assessment affects the speaking skills of the students in the Think-E course. The researcher focused on macro skills speaking because the teaching-learning process in Think-E uses communicative function according to situation, participants, and goals. The method used by the researcher is qualitative. The researchers collected the data through observation. The participants of this research were the students in Bee 2 class. The finding shows that there are three types of speaking assessment used in English language Teaching at the Think-E course, they are intensive assessment, responsive assessment, and interactive assessment. In conclusion, the assessment used in Think-E course affect the students dare to speak English and the students also get used to speaking English, so that they can speak English fluently.